SUSTAINABLE DEVELOPMENT STRATEGY: REVIEW OF GOVERNMENT POLICY IN MAINTAINING THE ENVIRONMENT - Fika Febriani (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2023)
Environmental conservation is a process or method of protection from damage and destruction that is carried out to maintain and protect nature and its components, as well as maintaining the balance of the ecosystem. The government has an important role in this effort through establishing policies that support environmental conservation, maintaining ecosystem balance, and ensuring the sustainability of natural resources. One focus of government policy is forest protection, where deforestation and illegal logging are considered serious problems. Forest rehabilitation programs and reforestation campaigns are integral strategies in maintaining forest sustainability. The government also implemented several policies, including Law no. 32 of 2009 concerning Environmental Protection and Management and Law no. 18 of 2008 concerning Waste Management, to overcome the negative impact of human activities on the environment. The government's role also includes implementing strict environmental regulations, especially in the industrial sector, with the aim of controlling and limiting the environmental impacts of economic activities and imposing sanctions on violators. Improving legal instruments, such as Law No. 32 of 2009 concerning Environmental Protection and Management, is one of the government's efforts to update environmental regulations. The success of environmental conservation also depends on the effectiveness of environmental institutions, which is reflected in the performance of government agencies, legal instruments and statutory regulations. The formation of this institution is an effort to preserve the environment through various programs run by the government.